Espacios naturales de ribera en el municipio de Zaragoza - Ollero Ojeda, Alfredo (Geographicalia, 2017)
Zaragoza city is crossed by the rivers Ebro, Gállego & Huerva, whose banks count on a total of 606 Has., which might be thought of as being natural spaces. Are search about ordenation in a natural means is undergone, taking into account the interest of riverside spaces in Zaragoza, their characteristics, location, the diagnosis of their situation nowedays and the resulting impacts, concluding with the setting of alternatives.